Mixed Vaginitis in the Third Trimester of Pregnancy Is Associated With Adverse Pregnancy Outcomes: A Cross-Sectional Study - Li, Huanrong; Dong, Mengting; Xie, Wenjuan; Qi, Wenhui; Teng, Fei; Li, Huiyang; Yan, Ye; Wang, Chen; Han, Cha; Xue, Fengxia (Frontiers in Cellular and Infection Microbiology, 2022)
Mixed vaginitis is a complex vaginal dysbiosis that differs from single vaginitis. Vaginitis in the third trimester may lead to adverse maternal and neonatal outcomes. The clinical characteristics, microbiological characteristics, and adverse pregnancy outcomes of mixed vaginitis in late pregnancy are worth studying. Therefore, this study investigated the clinical and microbiological characteristics of vaginitis and adverse pregnancy outcomes of patients with mixed vaginitis. We studied 1,674 women in late pregnancy who attended the Tianjin Medical University General Hospital from November, 2019 to October, 2021. We administered standardized questionnaires, performed vaginal examination and sampling plus microscope examinations, and assessed follow-up pregnancy outcomes. We cultured the vaginal discharge of the patients with mixed vaginitis to isolate pathogens and performed antimicrobial susceptibility tests of the isolated pathogens. For the patients with peripartum infection, we collected a sample to isolate pathogens. Among the 1,674 women, 66 (3.9%) had mixed vaginitis. The independent risk factor for mixed vaginitis in late pregnancy was a history of vaginitis during early and middle pregnancy (OR = 5.637, 95% CI: 3.314–9.580). The signs of vaginal erythema (63.6% vs. 42.0%), yellow discharge (81.8% vs. 59.6%), and malodor (31.8% vs. 18.8%) (P <0.05) were significantly higher in patients with mixed vaginitis than in patients with single vaginitis. Bacterial isolates of the vaginal secretions of patients with mixed bacterial vaginitis were mainly the pathogens of aerobic vaginitis and bacterial vaginosis, such as Gardnerella vaginalis, Streptococcus anginosus, and Staphylococcus epidermidis. Pathogen isolation of the vaginal secretions of patients with mixed fungus and bacteria vaginitis mainly included Candida albicans, followed by S. anginosus, Enterococcus faecalis, Staphylococcus hemolyticus, Staphylococcus aureus, Streptococcus agalactiae and Staphylococcus simulans. Women with mixed vaginitis had an increased incidence and risk of peripartum infections (6.1% vs. 1.4%, P <0.05; OR = 3.985, 95% CI:1.214–13.079). Escherichia coli is the main pathogen that causes peripartum infection. Mixed vaginitis in late pregnancy is characterized by a severe and complex phenotype, complex vaginal dysbiosis, and a long course of vaginal dysbiosis. This can lead to an increased incidence and risk of peripartum infection. Therefore, more attention should be paid to patients with mixed vaginitis in the third trimester of pregnancy.